Alleviation of colonic inflammation by Lypd8 in a mouse model of inflammatory bowel disease. (5th April 2021) - Hsu, Chiao-Ching; Okumura, Ryu; Motooka, Daisuke; Sasaki, Reo; Nakamura, Shota; Iida, Tetsuya; Takeda, Kiyoshi
Abstract: Dysfunction of the intestinal mucosal barrier causes inflammatory bowel diseases (IBDs). Indeed, mucosal barrier impairment in the gut of IBD patients results from decreased expression of barrier molecules. Ly6/Plaur domain containing 8 (Lypd8) segregates microbiota from the colonic epithelial layer. In this study, we found that Lypd8 − /− mice, in which flagellated bacteria invaded the mucosal surface of the colon, developed spontaneous colitis when dysbiosis was induced by a high-fat diet (HFD). On the basis of this finding, we assessed whether the application of human LYPD8 (hLYPD8) protein exhibiting the glycan-dependent inhibition of bacterial motility is effective in a colitis model. Oral and anal treatments with hLYPD8 protein ameliorate dextran sulfate sodium-induced colitis and HFD-induced colitis in Lypd8 − /− mice. These results indicate a therapeutic potential of hLYPD8 protein supplementation for IBD. Abstract : Lypd8 mediates effective protection from colitis